Alveolar type 2 progenitor cells for lung injury repair - Ayobami Matthew Olajuyin; Xiaoju Zhang; Hong‐Long Ji (2019)
Abstract Alveolar type 2 progenitor cells (AT2) seem closest to clinical translation, specifying the evidence that AT2 may satisfactorily control the immune response to decrease lung injury by stabilizing host immune-competence and a classic and crucial resource for lung regeneration and repair. AT2 establish potential in benefiting injured lungs. However, significant discrepancies linger in our understanding vis-à-vis the mechanisms for AT2 as a regime for stem cell therapy as well as essential guiding information for clinical trials, including effectiveness in appropriate pre-clinical models, safety, mostly specifications for divergent lung injury patients. These important gaps shall be systematically investigated prior to the vast therapeutic perspective of AT2 cells for pulmonary diseases can be considered. This review focused on AT2 cells homeostasis, pathophysiological changes in the pathogenesis of lung injury, physiological function of AT2 cells, apoptosis of AT2 cells in lung diseases, the role of AT2 cells in repairing processes after lung injury, mechanism of AT2 cells activation promote repairing processes after lung injury, and potential therapy of lung disease by utilizing the AT2 progenitor cells. The advancement remains to causally connect the molecular and cellular alteration of AT2 cells to lung injury and repair. Conclusively, it is identified that AT2 cells can convert into AT1 cells; but, the comprehensive cellular mechanisms involved in this transition are unrevealed. Further investigation is mandatory to determine new strategies to prevent lung injury.